The Leachate Release and Microstructure of the Sewage Sludge under the Anaerobic Fermentation - Yiqie Dong; Haijun Lu; Jixiang Li; Changhong Wang (Journal of Chemistry)
Pollutant release, pore structure, and thermal effect of sewage sludge during anaerobic fermentation were investigated. Results showed that the pH value firstly declined and then increased during anaerobic fermentation. The BOD5 and organics of sewage sludge declined, and the BOD5 of samples which was originally neutral declined as much as 53.6%. The micropore of samples was relatively developed. The biggest adsorption amount was 69.2 cm3/g. The average pore size was enlarged about 16.0–19.8% under anaerobic fermentation. There existed endothermic valley during heating procedure of 0–200∘C because of the dehydration, and the mass loss was 60.9–72.5%. The endothermic valley of the sample fluctuated at the 14th day in the anaerobic fermentation. During the heating procedure of 200–600∘C, there existed exothermal peaks because of the oxidation and burning of the organics. The curve of sample which was originally neutral had comparatively large endothermic valley and exothermal peak.